Differential microRNA Profiles and Their Functional Implications in Different Immunogenetic Subsets of Chronic Lymphocytic Leukemia - Nikos Papakonstantinou; Stavroula Ntoufa; Elisavet Chartomatsidou; Giorgio Papadopoulos; Artemis Hatzigeorgiou; Achiles Anagnostopoulos; Katerina Chlichlia; Paolo Ghia; Marta Muzio; Chrysoula Belessi; Kostas Stamatopoulos (BMC, 2013)
Abstract Critical processes of B-cell physiology, including immune signaling through the B-cell receptor (BcR) and/or Toll-like receptors (TLRs), are targeted by microRNAs. With this in mind and also given the important role of BcR and TLR signaling and microRNAs in chronic lymphocytic leukemia (CLL), we investigated whether microRNAs could be implicated in shaping the behavior of CLL clones with distinct BcR and TLR molecular and functional profiles. To this end, we examined 79 CLL cases for the expression of 33 microRNAs, selected on the following criteria: (a) deregulated in CLL versus normal B-cells; (b) differentially expressed in CLL subgroups with distinct clinicobiological features; and, (c) if meeting (a) + (b), having predicted targets in the immune signaling pathways. Significant upregulation of miR-150, miR-29c, miR-143 and miR-223 and downregulation of miR-15a was found in mutated versus unmutated CLL, with miR-15a showing the highest fold difference. Comparison of two major subsets with distinct stereotyped BcRs and signaling signatures, namely subset 1 [IGHV1/5/7-IGKV1(D)-39, unmutated, bad prognosis] versus subset 4 [IGHV4-34/IGKV2-30, mutated, good prognosis] revealed differences in the expression of miR-150, miR-29b, miR-29c and miR-101, all down-regulated in subset 1. We were also able to link these distinct microRNA profiles with cellular phenotypes, importantly showing that, in subset 1, miR-101 downregulation is associated with overexpression of the enhancer of zeste homolog 2 (EZH2) protein, which has been associated with clinical aggressiveness in other B-cell lymphomas. In conclusion, specific miRNAs differentially expressed among CLL subgroups with distinct BcR and/or TLR signaling may modulate the biological and clinical behavior of the CLL clones.